2006
DOI: 10.5465/amr.2006.20208684
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Citizenship: Creating Intangible Assets Across Institutional Environments

Abstract: We argue that citizenship programs are strategic investments comparable to R&D and advertising. They can create intangible assets that help companies overcome nationalistic barriers, facilitate globalization, and outcompete local rivals. Program content selection reflects a balance between legitimation and differentiation, and choices are influenced both by local institutional environments that shape expectations of corporate commitment to citizenship and by the degree of customization required because of inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
539
2
16

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 695 publications
(573 citation statements)
references
References 69 publications
(115 reference statements)
16
539
2
16
Order By: Relevance
“…Whereas earlier findings of Gardberg and Fombrun (2006), Melo and Garrido-Morgado (2012), and Lin et al (2016) showed that CSR improves reputation and that this reputational advantage motivates managers to pursue CSR (Brønn and Vidaver-Cohen, 2009;Babiak and Trendafilova, 2011), our results imply that if an SME starts CSR 9 Does CSR put reputation of SMEs at risk? activities, it creates more exposure to external criticism on its CSR.…”
Section: Implications For Csr Strategies Of Smescontrasting
confidence: 90%
“…Whereas earlier findings of Gardberg and Fombrun (2006), Melo and Garrido-Morgado (2012), and Lin et al (2016) showed that CSR improves reputation and that this reputational advantage motivates managers to pursue CSR (Brønn and Vidaver-Cohen, 2009;Babiak and Trendafilova, 2011), our results imply that if an SME starts CSR 9 Does CSR put reputation of SMEs at risk? activities, it creates more exposure to external criticism on its CSR.…”
Section: Implications For Csr Strategies Of Smescontrasting
confidence: 90%
“…CSR activity and shareholder value easily map onto observable variables, and we assert that a defensible link between CSR activity and goodwill has been established both theoretically (Gardberg and Fombrun, 2006;Godfrey, 2005) and empirically (Turban and Greening, 1997;Simon, 1995;Van Herpen et al, 2003;Williams and Barrett, 2000). The mens rea attribution process remains as an unobserved, and most likely unobservable, variable (Godfrey and Hill, 1995); unobservable because it is intrapsychic and may be a tacit or semiconscious process (Gladwell, 2005;Winter, 1987).…”
Section: Other Variablesmentioning
confidence: 65%
“…In particular, we investigate when participation in some types of CSR activities creates a form of goodwill or moral capital for the firm that acts as 'insurancelike' protection when negative events occur (Gardberg and Fombrun, 2006;Godfrey, 2005) that preserves shareholder value (CFP). Thus, this article investigates a different aspect of the CSR-CFP relationship; namely, that CSR activities can provide an insurance mechanism to preserve-rather than generate-CFP.…”
Section: Introductionmentioning
confidence: 99%
“…Tangible resources are linked to practical aspects, while intangible resources refer to immaterial resources and capacities, such as reputation and human capital (Halme and Korpela 2014). According to the RBV, these intangible assets are difficult to imitate or substitute (Barney 1991;Surroca et al 2010) and play a role in business' survival (Gardberg and Fombrun 2006).…”
Section: Smes Sd and Performancementioning
confidence: 99%